Electronic structure, Dirac points and Fermi arc surface states in three-dimensional Dirac semimetal Na3Bi from angle-resolved photoemission spectroscopy*Project supported by the National Natural Science Foundation of China (Grant No. 11574367), the National Basic Research Program of China (Grant Nos. 2013CB921700, 2013CB921904, and 2015CB921300), and the Strategic Priority Research Program (B) of the Chinese Academy of Sciences (Grant No. XDB07020300). The synchrotron radiation experiments have been done under the HiSOR Proposal numbers, 12-B-47 and 13-B-16. (10th June 2016) - Liang 梁, Aiji 爱基; Chen 陈, Chaoyu 朝宇; Wang 王, Zhijun 志俊; Shi 石, Youguo 友国; Feng 冯, Ya 娅; Yi 伊, Hemian 合绵; Xie 谢, Zhuojin 卓晋; He 何, Shaolong 少龙; He 何, Junfeng 俊峰; Peng 彭, Yingying 莹莹; Liu 刘, Yan 艳; Liu 刘, Defa 德发; et al.
Abstract: The three-dimensional (3D) Dirac semimetals have linearly dispersive 3D Dirac nodes where the conduction band and valence band are connected. They have isolated 3D Dirac nodes in the whole Brillouin zone and can be viewed as a 3D counterpart of graphene. Recent theoretical calculations and experimental results indicate that the 3D Dirac semimetal state can be realized in a simple stoichiometric compound A 3 Bi ( A = Na, K, Rb). Here we report comprehensive high-resolution angle-resolved photoemission (ARPES) measurements on the two cleaved surfaces, (001) and (100), of Na3 Bi. On the (001) surface, by comparison with theoretical calculations, we provide a proper assignment of the observed bands, and in particular, pinpoint the band that is responsible for the formation of the three-dimensional Dirac cones. We observe clear evidence of 3D Dirac cones in the three-dimensional momentum space by directly measuring on the k x – k y plane and by varying the photon energy to get access to different out-of-plane k z s. In addition, we reveal new features around the Brillouin zone corners that may be related with surface reconstruction. On the (100) surface, our ARPES measurements over a large momentum space raise an issue on the selection of the basic Brillouin zone in the (100) plane. We directly observe two isolated 3D Dirac nodes on the (100) surface. We observe the signature of the Fermi-arc surface states connecting the two 3D Dirac nodes that extend to a binding energy of ∼150 meV before merging into the bulk band. Our observations constitute strong evidence on the existence of the Dirac semimetal state in Na3 Bi that are consistent with previous theoretical and experimental work. In addition, our results provide new information to clarify on the nature of the band that forms the 3D Dirac cones, on the possible formation of surface reconstruction of the (001) surface, and on the issue of basic Brillouin zone selection for the (100) surface.